Strategic Management Of School Principals In Improving The Achievement Of Islamic Religious Education - Irpan Ilmi; Euis Hayyun Thoyibah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The achievement of Islamic Religious Education (PAI) in elementary schools continues to face various challenges, particularly due to the suboptimal implementation of principals’ strategic management in improving the quality of learning and student achievement. This condition highlights the importance of strategic leadership that effectively integrates planning, monitoring, analysis, and continuous evaluation. This study aims to examine the principal’s strategic management in improving Islamic Religious Education (PAI) achievement at SDN Jadimulya Cikalong. The study employed a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation and analyzed using descriptive qualitative techniques. The findings reveal that the principal implemented strategic management systematically and collaboratively through data-driven program planning, regular monitoring of program implementation, comprehensive analysis of program outcomes, and continuous evaluation involving teachers, students, and parents. These strategies have proven effective in improving both students’ academic achievement and religious character, as evidenced by their accomplishments at the village and sub-district levels. The findings underscore that improving Islamic Religious Education achievement depends largely on the implementation of adaptive, collaborative, and sustainable strategic management. This study contributes to the literature on educational leadership by providing empirical evidence on the role of principals’ strategic management in enhancing the quality of Islamic Religious Education in elementary schools.